KONSEP PENATAAN KELUARGA SAKINAH DALAM PERSPEKTIF FIQH MUNAKAHAT - Supardi Mursalin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
This study describes the concept of sakinah family arrangement from the fiqh of munakahat perspective. In a sakinah household, it takes a partner who understands the duties, rights and obligations. This research is a literature study that uses documentation techniques to collect research data. While the analysis technique used is descriptive. After conducting an in-depth research study, it was concluded that the arrangement of the sakinah family in the perspective of fiqh munakahat has several principles, including the principle of freedom in choosing a partner, the principle of mawaddah wa rahmah (love and affection), the principle of complementing and protecting each other, and the principle of mu'asyarah bi al-ma'ruf. While the indicators of a sakinah family include the emergence of mutual understanding, mutual love, acceptance, respect and love between people who live in a family based on responsibility. It basically can create an atmosphere of harmony and harmony in a household.